PROBLEMS OF ARCHAEOLOGICAL TOURISM DEVELOPMENT IN NAMANGAN REGION - Durdona Mahmudova (American Journals Publishing, 2023)
This article systematically analyzes the prospects for the development of archaeological tourism in the Namangan region and the problems in the field. The main focus of the article is on the tourist opportunities of the Namangan region, the implementation of government decisions on the development of archaeological tourism in the region, and the current manifestations of the attitude towards archaeological objects.
Keywords: Namangan region, tourism, archaeological tourism, Aksikent, Munchogtepa, Mugtepa, tourist opportunities, tourist services.